2021
DOI: 10.1111/tbed.14278
|View full text |Cite
|
Sign up to set email alerts
|

Feline morbillivirus‐1 in dogs with respiratory diseases

Abstract: Feline morbillivirus‐1 (FeMV‐1) is a viral pathogen associated with kidney disease in domestic cats and wild felids. We initially identified the FeMV‐1 from the lung of a necropsied dog with severe pulmonary disease by the reverse transcription polymerase chain reaction (RT‐PCR). Thereafter, we investigated FeMV‐1 in nasal and oral swab samples from 73 healthy and 113 dogs with respiratory illnesses. We found polymerase chain reaction (PCR)‐positive FeMV‐1 from only 14/113 (12.39%) dogs with respiratory diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…4,22 The identified FeMV-1A genotype also had in vivo tropism for various epithelial cells in the trachea, bronchi, bronchioles, kidneys, and urinary bladder, suggesting the epitheliotropism of FeMV. 12 FeMV immunoreactivity was also evident in the cytoplasm of lymphoid cells in the spleen and lymph nodes, supporting the lymphotropic nature of FeMV that was recently described. 10 Moreover, viral antigen was also detected in astroglia and oligodendroglia cells in the brain, supporting FeMV neurotropism as for other morbillivirus infection.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…4,22 The identified FeMV-1A genotype also had in vivo tropism for various epithelial cells in the trachea, bronchi, bronchioles, kidneys, and urinary bladder, suggesting the epitheliotropism of FeMV. 12 FeMV immunoreactivity was also evident in the cytoplasm of lymphoid cells in the spleen and lymph nodes, supporting the lymphotropic nature of FeMV that was recently described. 10 Moreover, viral antigen was also detected in astroglia and oligodendroglia cells in the brain, supporting FeMV neurotropism as for other morbillivirus infection.…”
supporting
confidence: 88%
“…To confirm the concordant results of viral-like particles by TEM and FeMV nucleic acid detected by RT-qPCR, the kidney sections of both cats were subjected to immunohistochemistry (IHC) to determine the presence of FeMV antigen using Pab-His-rFeMV-M. 10,12 Prominent FeMV immunoreactivity was localized in renal tubular epithelial cells, where the eosinophilic, intracytoplasmic, hyalinized globular materials were found (Fig. 4, inset).…”
mentioning
confidence: 84%
“…Nasal and oral swabs from dogs with respiratory disease in Thailand were tested reverse transcriptase-polymerase chain reaction (RT-PCR) positive for FeMV RNA, and FeMV-GT1 was subsequently isolated from swabs and lung samples of a dead dog [38]. The FeMV-GT1 sequences obtained in this study showed 97.5-99.2% identity with sequences derived from domestic cats in Thailand, Hong Kong, and Japan.…”
Section: Virus Properties and Host Spectrummentioning
confidence: 86%
“…Another interesting point concerns the possible cross-reaction of other Morbilliviruses . Even though CDV is the only canine-specific Morbillivirus , recently, a new Morbillivirus that usually infect cats (namely feline morbillivirus-1, FeMV-1) was rarely isolated from dogs that present with respiratory diseases [ 23 ]. This virus has been isolated also in cats in Northern Italy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%